1996
DOI: 10.1056/nejm199602013340501
|View full text |Cite
|
Sign up to set email alerts
|

Mismatches of Minor Histocompatibility Antigens between HLA-Identical Donors and Recipients and the Development of Graft-Versus-Host Disease after Bone Marrow Transplantation

Abstract: A mismatch of minor histocompatibility antigen HA-1 can cause GVHD in adult recipients of allogeneic bone marrow from HLA-identical donors. Prospective HA-1 typing may improve donor selection and identify recipients who are at high risk for GVHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
330
2
9

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 567 publications
(355 citation statements)
references
References 20 publications
10
330
2
9
Order By: Relevance
“…Nevertheless, it has long been established that alloreactivity against MHC molecules is not the only factor conditioning GVHD since the 1-3% occurrence of DR/DQ and DP recombination cannot account for the 20-50% of GVHD reported between genotypically identical siblings (1). Moreover, the contribution of minor histocompatibility antigens to the increased risk of GVHD has been recently demonstrated (19). Because minor histocompatibility antigens disparity is bound to be significantly greater between unrelated than between genoidentical individuals (20), it is likely that specific T cells directed against minor antigens also contribute to the increased risk of GVHD after unrelated bone marrow transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has long been established that alloreactivity against MHC molecules is not the only factor conditioning GVHD since the 1-3% occurrence of DR/DQ and DP recombination cannot account for the 20-50% of GVHD reported between genotypically identical siblings (1). Moreover, the contribution of minor histocompatibility antigens to the increased risk of GVHD has been recently demonstrated (19). Because minor histocompatibility antigens disparity is bound to be significantly greater between unrelated than between genoidentical individuals (20), it is likely that specific T cells directed against minor antigens also contribute to the increased risk of GVHD after unrelated bone marrow transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…7 In BMT that are MHC matched but mHA disparate, donor T cells still recognize MHC peptide derived from the products of recipient polymorphic genes, the mHAs. [8][9][10] The expression of mHAs is wide and variable. Thus, different mHAs might dictate variable phenotype, target organ involvement, development kinetics of GVHD and antitumor responses after allogeneic BMT.…”
Section: Triggers For Induction Of Gvhdmentioning
confidence: 99%
“…However, these findings do not necessarily imply a role for these MiHAs in GVHD, because host reactive anti-MiHAs CTLs were found with similar frequencies in patients with or without GVHD (35). Goulmy et al have recently reported that a mismatch of HA-1 MiHA, whose molecular structure is unknown, was associated with an increased rate of GVHD in adult recipients of bone marrow transplants (36). Thus, HA-1 is heretofore the only MiHA that has been implicated in GVHD.…”
Section: Discussionmentioning
confidence: 99%